First volatile inventory for Gorely volcano, Kamchatka - AIUPPA, Alessandro; TAMBURELLO, Giancarlo; CALABRESE, Sergio; Giudice, G; Liuzzo, M; Allard, P; Chaplygin, I; McGonigle, AJS; Taran, Y. (Geophysical Research Letters, 2012)
We report here the very first assessment of volatile flux emissions from Gorely, an actively degassing volcano in Kamchatka. Using a variety of in situ and remote sensing techniques, we determined the bulk plume concentrations of major volatiles (H2O 93.5%, CO2, 2.6%, SO2 2.2%, HCl 1.1%, HF 0.3%, H2 0.2%) and trace-halogens (Br, I), therefore estimating a total gas release of 11,000 tons·day−1 during September 2011, at which time the target was non-eruptively degassing at 900°C. Gorely is a typical arc emitter, contributing 0.3% and 1.6% of the total global fluxes from arc volcanism for CO2 and HCl, respectively. We show that Gorely's volcanic gas (H2O/SO2 43, CO2/SO2 1.2, HCl/SO2 0.5) is a representative mean end-member for arc magmatism in the north-west Pacific region. On this basis we derive new constraints for the abundances and origins of volatiles in the subduction-modified mantle source which feeds magmatism in Kamchatka.